The normative dimension of linguistic and rhetorical systems in the Arabic language - Ra'dan, Abdul Karim Hussein Ali (Journal of Humanities & Social Sciences, 2019)
This study aims to investigate the normative dimensions of the Arabic grammar both linguistic and rhetorical structures. It explores their rules and functions. The linguistic rules include parsing, sentence order, agreement, derivation and synonyms. The rhetorical rules encompass the antonyms, contrast, rhythm and the imagery. These grammatical rules constitute normative bases in the Arabic language and they complement each other. They perform connotation functions, remove ambiguity, and they put lexicons in order in the sentence according to connotations and aesthetic norms and contexts. The study further aims to enrich the Arabic language and its lexicon to meet the overall communicative goal creating creative texts and daily argumentative discourses which fulfill the functions of persuasion and entertaining.
Keywords: regulations; normative; linguistic; rhetorical; Arabic